MAIN FACTORS INFLUENCING MEADOWY PHYTOCENOSIS OF LEFT-BANK FOREST-STEPPE AREA OF UKRAINE - Орлова, Л.Д. (World of Medicine and Biology, 2012)
There was characterized the effect of biotic and abiotic natural and anthropogenic factors was. It was noted that the geologic structure, parent rock material, soil types, climate, rainfalls can be refered to main abiotic characteristics that meadows have been effected by; the main biotic factors are phytocenosis, zoocenosis and microbocenosis; anthropogenic effects is discernible mostly through economic and legal relations, practical use directions, more often as hayfields, pastures, and technogenic emergences. It was emphasized that the factors influence each other and more often work in a complex.